Are computed tomography 3D measurements of the upper airways in mouth-breathing children in agreement with the ENT clinical diagnosis of obstruction? - Vidigal,Bruno César Ladeira (2019)
Abstract Introduction: Imaging studies have hystorically been used to support the clinical otorhinolaryngological evaluation of the upper respiratory tract for the diagnosis of obstructive causes of oral breathing. Objective: The objective of this study was to compare 3D volumetric measurements of nasal cavity, nasopharynx and oropharynx of obstructed mouth-breathing children with measurements of non-obstructed mouth-breathing children. Methods: This retrospective study included 25 mouth-breathing children aged 5-9 years evaluated by otorhinolaryngological clinical examination, flexible nasoendoscopy and full-head multi-slice computed tomography. Tomographic volumetric measurements and dichotomic otorhinolaryngological diagnosis (obstructed vs. non-obstructed) in three anatomical regions (the nasal cavity, nasopharynx and oropharynx) were compared and correlated. An independent sample t-test was used to assess the association between the 3D measurements of the upper airways and the otorhinolaryngological diagnosis of obstruction in the three anatomical regions. Inter- and intra-observer intraclass correlation coefficients were used to evaluate the reliability of the 3D measurements. Results: The intra-class correlation coefficients ranged from 0.97 to 0.99. An association was found between turbinate hypertrophy and nasal cavity volume reduction (p < 0.05) and between adenoid hyperplasia and nasopharynx volume reduction (p < 0.001). No association was found between palatine tonsil hyperplasia and oropharynx volume reduction. Conclusions: (1) The nasal cavity volume was reduced when hypertrophic turbinates were diagnosed; (2) the nasopharynx was reduced when adenoid hyperplasia was diagnosed; and (3) the oropharynx volume of mouth-breathing children with tonsil hyperplasia was similar to that of non-obstructed mouth-breathing children. The adoption of the actual anatomy of the various compartments of the upper airway is an improvement to the evaluation method.